(untitled) (European Journal of Economics, Finance and Business Development, 2024)
The green economy represents a paradigm shift towards sustainability, prioritizing environmental health alongside economic growth. This article explores the foundations and evolution of the green economy, highlighting critical sectors such as renewable energy and sustainable agriculture. Through an analysis of policies and strategies, the paper identifies challenges and offers solutions to overcome barriers. Case studies illustrate successful transitions, providing a roadmap for future efforts. The green economy is crucial for mitigating climate change and fostering global sustainability.